Exploring a Software Framework for Posture Tracking and Haptic Feedback Control: A Virtual Reality-Based Approach for Upper Limb Rehabilitation on the Oculus Quest 2 - Joaquin Dillen; Antonio H. J. Moreira; João L. Vilaça (Sensors)
Virtual reality (VR) has gained significant attention in various fields including healthcare and industrial applications. Within healthcare, an interesting application of VR can be found in the field of physiotherapy. The conventional methodology for rehabilitating upper limb lesions is often perceived as tedious and uncomfortable. The manual nature of the process, performed by physicians, leaves patients in an environment lacking motivation and engagement. This presents an opportunity for implementing VR as a tool to enhance the rehabilitation process and improve the quality, efficiency, and evolution of recovery. However, physiotherapy often lacks relevant data to track the recovery process effectively, further compounding concerns about its efficacy. To address this, we propose the development of a posture control system using the Oculus Quest 2, a VR device. Our primary objective was to validate the performance aspects of this device and assess its potential as a rehabilitation tool, providing valuable support to healthcare professionals. Through a series of tests, we evaluated the effectiveness of our VR solution by integrating it into specific therapeutic exercises. This approach enhances patient involvement by offering real-time feedback on exercise execution and providing clear instructions for posture correction. The results demonstrate a notable impact on exercise performance, highlighting the feasibility of developing physiotherapeutically adapted solutions utilizing VR technology. By leveraging the Oculus Quest 2 system and the proposed framework, our research contributes to the advancement of VR-based rehabilitation practices. The findings offer valuable insights into the potential benefits of integrating immersive technologies into the field of physiotherapy, empowering healthcare professionals in their treatment approaches.